2013
DOI: 10.1186/1477-7525-11-121
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of psychosocial interventions for cancer patients undergoing radiotherapy

Abstract: BackgroundMany patients with cancer experience depression and anxiety, and an associated decrease in quality of life (QOL) during radiation therapy (RT). The main objective of the study was to determine the benefits of psychosocial interventions for cancer patients who received RT.MethodsPatients with cancer (n = 178) who agreed to participate in the study were randomized to the intervention arm (n = 89) or the control arm (n = 89). Patients in the intervention group received psychosocial care during RT, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 49 publications
(47 reference statements)
4
86
0
1
Order By: Relevance
“…47, 48 Although, most research focuses on patient interventions, care partner interventions have been found to not only help the care partner but also the patient in decreasing negative outcomes such as depression, anxiety, and distress. 49, 50 Nurses should institute the help of family members in assessing for acute cognitive/affective alterations, which might prove to reduce the anxiety of family members while improving outcomes for the patient. Finally, the trajectories, breadth and depth of cognitive/affective symptoms has yet to be described, which is an essential for the advancement of cognitive/affective symptom science in the IL-2 population.…”
Section: Implications For Practicementioning
confidence: 99%
“…47, 48 Although, most research focuses on patient interventions, care partner interventions have been found to not only help the care partner but also the patient in decreasing negative outcomes such as depression, anxiety, and distress. 49, 50 Nurses should institute the help of family members in assessing for acute cognitive/affective alterations, which might prove to reduce the anxiety of family members while improving outcomes for the patient. Finally, the trajectories, breadth and depth of cognitive/affective symptoms has yet to be described, which is an essential for the advancement of cognitive/affective symptom science in the IL-2 population.…”
Section: Implications For Practicementioning
confidence: 99%
“…Still others adopted eclectic approaches involving psychoeducation, cognitive-behavioral therapy, and supportive expressive therapy for patients receiving radiotherapy. 10 Depression, anxiety, and health-related quality of life improved in the experimental groups, particularly for female patients receiving a high dose of radiotherapy and who had previously received adjuvant chemotherapy. Although they have exhibited no proven effect on survivorship, the few interventions for patients undergoing radiotherapy epitomize the psychosocial needs of this cohort.…”
mentioning
confidence: 98%
“…Educating patients about their disease, its treatment, potential side effects, and qol can reduce anxiety 8 , enhance coping mechanisms 9 , reduce decisional conflicts, promote patient autonomy, and improve the patient experience 10 . Patients who understand their disease and its treatment also comply better with therapy 11 , which translates into better outcomes.…”
Section: Introductionmentioning
confidence: 99%